Polimorfismo do códon 72 (arg e pro) do gene TP53 por PCR em tempo real em pacientes pediátricos infectados por helicobacter pylori - Venerando, Roberto (2012)
Chronic infection with H. pylori is acquired in childhood, and in the absence of appropriate antibiotics usually persists for life, which is the main etiologic factor of gastritis and peptic ulcer. Chronic infection by the bacteria leads to increased rates of apoptosis, which may accelerate the progression to atrophic gastritis, with consequent increased risk for developing gastric cancer. The cells can still undergo apoptosis in response to internal signals, including DNA damage, with the participation of genes involved in cell cycle control, such as tumor suppressor gene TP53. This gene, determined as the "guardian of the genome" plays an importante role in maintaining the integrity of DNA and induction of apoptosis, eliminating selectively, damaged cells, and protecting the organism from cancer development. Polymorphism of the tumor suppressor gene TP53, codon 72, has been investigated extensively to verify its association to cancer worldwide. This work was propositions: to determine the genotype and allele frequency of the TP53 polymorphism at códon 72 (Arg and Pro) and polymorphic variations correlate with age and histopathological findings in samples of DNA extracted earlier biopsy of the gastric mucosa of patients infected and uninfected pediatric H. pylori by polymerase chain reaction in real time. Three hundred and forty-two patients participated in the study, DNA was extracted from gastric biopsy and detection of H. pylori was performed by PCR allelic to discrimination of the SNP rs1042522 (TP53), was performed by polymerase chain reaction in real time. The results showed no statistically significant difference between gender and TP53 gene polymorphism compared with the positivity of H. pylori. However there was a statistically significant association between age and positive for H. pylori. It was found that patients aged ≤ 10 years were 1.3 times more likely to have infection by H. pylori when compared with patients aged> 10 years